The media in campaign or the rise of the voters: Peru, presidential elections 2006 - Pedraglio, Santiago (2008)
This is an opinion and research article about the media behavior in the Peruvian presidential elections of 2006; it revolves around the agreements and disagreements between the media, the candidates and the voters. The article’s main goal is to analyze media behavior during the last months of the electoral first round; at the same time, it explains the media and candidates performance in order to get close to the place were the citizen political opinions are build.